PENERAPAN FENG SHUI BA ZHAI PADA TATA RUANG WARISAN ARSITEKTUR TIONGHOA RUMAH TJONG A FIE: APPLICATION OF FENG SHUI BA ZHAI TO THE SPATIAL PLANNING OF CHINESE ARCHITECTURAL HERITAGE OF TJONG A FIE’S HOUSE - Makmur Iknu Wijaya; Sangayu Ketut Laksemi Nilotama (Jurnal Seni dan Reka Rancang: Jurnal Ilmiah Magister Desain, 2024)
The Industrial Revolution not only facilitated extensive natural resource exploitation but also introduced concepts like “harmonization of nature,” ethnic development, and global migration. Among the groups affected was the Tionghoa ethnic community, which migrated from Asia to the West, including Indonesia (Nusantara), while carrying their cultural heritage. The Tjong A Fie Mansion in Medan, Indonesia, serves as a significant architectural artifact, reflecting the principles of Traditional Chinese Architecture Philosophy. This study explores how the mansion embodies these principles, conveying messages and meanings within its architectural patterns. Employing an interdisciplinary approach rooted in cultural studies, this research incorporates the Feng Shui Ba Zhai framework. The methodology includes: 1) collection and classification of data related to the mansion’s cultural and architectural context; 2) analysis and interpretation of its structural elements; and 3) conclusions regarding the messages and meanings conveyed by the architecture. The findings reveal that the Tjong A Fie Mansion utilizes key elements—such as dividing walls, jian (rooms), axis alignment, space orientation, and courtyards—aligned with Feng Shui Ba Zhai principles. Ultimately, this study highlights how cultural messages are preserved through architecture, emphasizing the mansion’s significance as a historical and cultural legacy.